Pola Interaksi Orang Tua dan Anak di Perkotaan Dalam Menghadapi Dampak Negatif Penggunaan Gadget - Savitri, Galuh Ayu; Kholis, Nur; Zunaidah, Asih (Universitas Merdeka Madiun, 2019)
The uses of gadget have become popular across generation, no exception with early childhood. Nowadays, parents in big cities can easily provide gadget to their children with variety of purposes, starting to maintain communication to the means of entertaining themselves. Unfortunately, it will result a negative effect such as an addiction and impact on interaction patterns with parents. This qualitative research study aims to explore and form patterns of interaction between parents and children that are ideal to face the negative effects of using gadget. This research is located in Malang City since it is the second major city in East Java with the high level of gadget use among early childhood, meanwhile in-depth interviews and observations are chosen to get the data. The study found that early childhood in Malang city have become addicted to gadget for several reasons. First of all, they tend to not care about the environment. Secondly, they make gadgets as a condition to do something so they could not obey the orders of parents, receive information well and unable to communicate with parents. Lastly children often play freely with gadgets without time constraints so they do not have time to build harmonious relationships with parents. This study suggests associative-based associative patterns to face the problem. The interaction pattern includes collaboration, accommodation and assistance with the principles of openness, empathy, supportive attitude, positive attitude and equality.